Enlisting faith : how the military chaplaincy shaped religion and state in modern America - Stahl, Ronit Y., 1980- (Harvard University Press, 2017)
A century ago, as the United States prepared to enter World War I, the American military chaplaincy included only mainline Protestants and Catholics. Today it counts Jews, Mormons, Muslims, Christian Scientists, Buddhists, Seventh-day Adventists, Hindus, and evangelicals among its ranks. Enlisting Faith traces the uneven processes through which the military struggled with, encouraged, and regulated religious pluralism over the twentieth century. Despite the constitutional separation of church and state, the federal government formally authorized and managed religion in the military. While officials debated which chaplains could serve, what insignia they would wear, and what religions soldiers could mark on dog tags, clergy in uniform figured out how to lead worship for and teach character education to a broad range of faiths, confronted racial discrimination and rape, wrestled with untimely death and proselytizing, and navigated conscientious objection to war. Enlisting Faith is a vivid, lively portrayal of religious encounters, state regulation, and the trials of faith--in God and country--experienced by the millions of Americans who fought in and with the armed forces in modern America.--